Geological Effect on GPR System Due to Soil Properties in Malaysia - A Karim, M.N; Jamlos, M.A; Ibrahim, S.Z; Jamlos, M.F; Lee, Y.S (International Journal of Integrated Engineering, 2019)
This paper present the measurement of dielectric properties of soil in Malaysia in three differences condition which are normal condition (ambience), heated (up to 50 OC) and wet condition (10 % water content). Eight (8) samples of soil have been collected in the local region and was measured in the frequency range from 0.5 GHz to 3.5 GHz for Ground Penetrating Radar (GPR) applications. The measurement of the dielectric properties has been conducted using Agilent high temperature probe (Model) integrated with Performance Network Analyzer (PNA E8362B). The uncertainties in measurement process, especially dealing with measurement data have been considered in order to eliminate the probability of error during the measurement. The measured result for permittivity and loss factor of the measured samples are tabulated in graphs and the analysis of the measured data are discussed in this paper.